KEEFEKTIFAN PROGRAM MATRIKULASI BAHASA UNTUK MENINGKATKAN KEMAMPUAN SPEAKING MAHASISWA STAIBN TEGAL - Pindha Kaptiningrum; Zaki Mubarok (Center of Language and Cultural Studies, 2017)
This study evaluates English matriculation program at Language Center STAIBN Tegal. Evaluation focused on (1) objective and process of the matriculation program, (2) progress of speaking ability of the learners, and (3) benefits and obstacles of the program. This study used formative evaluation design whose steps included: defining reasons for the evaluation, selecting evaluation model, identifying source persons, planning components of evaluation, defining questions for evaluation, planning evaluation design and schedule of implementation, data collection and analysis, and reporting the results. Data were collected using questionnaire, observation, and interview. This study revealed that matriculation program needs to be improved its objective and process. Progress of speaking achievement was salient, indicated by successful implementation of cooperative learning. Listening, reading and writing were not specified in the program. Benefits of the program indicated that students’ motivation was high, but restricted time allotments, facilities, and curriculum design appeared as chief obstacles.